'Plus ça Change, Plus C'est la Même Chose': Music Promoting, Digital Leisure, Social Media and Community. (4th July 2018) - Henderson, Stephen; Spracklen, Karl
ABSTRACT: This article draws from interviews with music promoters from the northern England to consider their use of social media to develop online communities. It reveals they have developed online spaces offering digital leisure for the making and enjoying of music, but the forming of these music-loving communities is problematic. Promoters are necessarily distracted by what might be called a corporate community of agents, local councils, and so forth. Promoting itself is complicated by the social community of live music fans with its different music genre-based subcommunities. As a result, complex community structures form around "pools, " "webs, " and "hubs" with whom the promoters communicate in both instrumental and communicative ways. Underpinning this social construct, activity in the community is predominantly transactional and instrumental in an approach that differs little from the equivalent offline world and, as a result, offers little as a transformative space for social justice.